ANALISIS KEPUASAN KONSUMEN BERDASARKAN VOICE OF CUSTOMER - Adhilla, Fitroh (Jurnal Analisis Bisnis Ekonomi, 2009)
Building customer relationships is a top priority in many firms. Building relationship with customers is to increase satisfaction and loyalty, increase the amount of favorable word of mouth, and purchases. Customers who have relationships with service provider not only expect to receive satisfactory delivery of the core service, but they are likely to receive additional benefits from the relationship. This research examines service quality at faculty of economic University of Ahmad Dahlan Yogyakarta with satisfaction. The population are undergraduate of management programme and use the convenience sampling with 100 respondence. The SERVQUAL includes reliability, responsiveness, assurance, empathy, and tangibles. Analysis method used to multiple regression.